Manipulating the levels of ethyl acetate and isoamyl acetate formation during the production of wine and brandy - Bayly, Jennifer Carr,1977- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2002.